2007
DOI: 10.1007/s00464-007-9300-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy with carbon dioxide pneumoperitoneum is safe even for high-risk patients

Abstract: For LC for patients with an ASA 3 and 4 risk for anesthesia, no significant adverse effects could be attributed to CO(2 )pneumoperitoneum. For high-risk patients, preoperative preparation and active perioperative monitoring are essential for safe anesthesia for LC with or without CO(2)PP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 24 publications
2
23
0
2
Order By: Relevance
“…In spite of the precautions, one patient had bled profusely from an open sinus in liver bed and had to be converted. Similar results have been cited by other authors previously [8][9][10][11].…”
Section: Discussionsupporting
confidence: 92%
“…In spite of the precautions, one patient had bled profusely from an open sinus in liver bed and had to be converted. Similar results have been cited by other authors previously [8][9][10][11].…”
Section: Discussionsupporting
confidence: 92%
“…Mimica et al (34) reported that the open technique was associated with a higher risk of anesthesia-related complications in the postoperative period as compared to LC. Koivusalo et al (35) reported that pneumoperitoneum was not associated with an additional risk in ASA III and ASA IV elderly patients during LC. Luo et al (36) concluded that LC is beneficial for restoration of stress hormones, nitrogen balance, and energy metabolism but that it may also cause acidemia and pulmonary hypoperfusion due to pneumoperitoneum.…”
mentioning
confidence: 98%
“…For example, the beneficial effects of low-pressure procedures on liver function were demonstrated in some studies (13)(14)(15). However, some studies showed the side effects of low-pressure and standardpressure pneumoperitoneum in laparoscopic cholecystectomy on different organs are comparable (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%